THE ROLE OF LEADERSHIP MODERATION ON FIXED ASSET MANAGEMENT SYSTEMS - Kuddy, Aprianto La'lang; Titalessy, Pisi Bethania; Agustin, Sheilla Putri; Murwaniputri, Hesti (Veredas do Direito, 2026)
This study aims to analyze and demonstrate how HR competency, internal control systems (ICS), and asset information technology influence the effectiveness of fixed asset management. Furthermore, it explores leadership's moderating role in the relationship between these three variables and fixed asset management effectiveness at Cenderawasih University. This study adopted a quantitative approach utilizing a survey method. Through questionnaire distribution, employing a purposive sampling technique, 150 employees directly involved in the fixed asset management process were sampled. This process includes planning, procurement, use, maintenance, security, utilization, assessment, disposal, administration, coaching, control, and supervision. The collected data were then analyzed using Structural Equation Modeling. The results empirically demonstrate that HR competency, ICS, and asset information technology partially influence the effectiveness of fixed asset management. Leadership, on the other hand, is proven to strengthen the influence of competency and information technology utilization on the effectiveness of fixed asset management. However, the interaction between leadership and the ICS showed no significant effect.